Prevalence of intestinal parasites in preschool children from the Angostura del Orinoco municipality, Bolívar state, Venezuela. 2016-2018 - Rodolfo Antonio Devera; Iván Dario Amaya-Rodríguez; Ytalia Yanitza Blanco-Martínez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
The objective of the present investigation was to determine the prevalence of intestinal parasites in preschool children users of 12 Simoncito Initial Education Centers (CEIS) of the Angostura del Orinoco municipality, Bolívar state, Venezuela. The feces of 515 children of both genders (2 to 5 years old) were studied using the spontaneous sedimentation technique. The prevalence of enteroparasites was 39.4% (n = 203). There were no statistically significant differences (χ2 = 1.59 d.f .: 2 p> 0.05) with respect to age but if according to gender (p <0.05), because the most affected were male child with 46.9%. Eleven taxa of enteroparasites were identified, highlighting the chromist Blastocystis spp. (27.4%) and the protozoan Giardia intestinalis (13.2%). A low prevalence of helminths was found, where Ascaris lumbricoides was the most common with 1.6%. Of the 203 parasitized children, 70.9% (n = 144) were monoparasitized and 29.1% (n = 59) polyparasitized. The main associated parasites were Blastocystis spp. (89.8%), G. intestinalis (44.1%) and Endolimax nana (35.3%). In conclusion, a high prevalence of intestinal parasites was determined in the population studied, so these infections continue to be a public health problem in children from Ciudad Bolívar, Venezuela